Characterizing prostate cancer risk through multi-ancestry genome-wide discovery of 187 novel risk variants - Wang, A; Shen, J; Rodriguez, AA; Saunders, EJ; Chen, F; Janivara, R; Darst, BF; Sheng, X; Xu, Y; Chou, AJ; Benlloch, S; Dadaev, T; et al. (Springer Nature, 2023)
The transferability and clinical value of genetic risk scores (GRSs) across populations remain limited due to an imbalance in genetic studies across ancestrally diverse populations. Here we conducted a multi-ancestry genome-wide association study of 156,319 prostate cancer cases and 788,443 controls of European, African, Asian and Hispanic men, reflecting a 57% increase in the number of non-European cases over previous prostate cancer genome-wide association studies. We identified 187 novel risk variants for prostate cancer, increasing the total number of risk variants to 451. An externally replicated multi-ancestry GRS was associated with risk that ranged from 1.8 (per standard deviation) in African ancestry men to 2.2 in European ancestry men. The GRS was associated with a greater risk of aggressive versus non-aggressive disease in men of African ancestry (P = 0.03). Our study presents novel prostate cancer susceptibility loci and a GRS with effective risk stratification across ancestry groups.